Pert/Cost Resource Allocation Procedure. - Ross, W. R. (The Accounting Review, 1966)
The article focuses on different approaches of managing the costs involved in large and complex programs of work like weapon systems, space ventures, etc. Structurally, the pert/cost system is based upon three interrelated components–a work breakdown structure, work packages, and the network. It is designed to provide management with the tools necessary to achieve schedule and cost planning, determination, and control in those instances for which conventional management systems are inadequate. The resource allocation procedure, a supplement to the basic Pert/Cost system, is concerned with the problem of efficient allocation of limited resources in accomplishing work programs, and is based on the premise that activities on a network are subject to time/cost trade-offs. This supplement is not considered an essential part of the Pert/Cost system. However, it serves to extend the usefulness and effectiveness of the Pert/Cost system as a management tool. While the concepts involved appear relatively simple, the implementation of the supplement usually requires considerable management education and understanding in order to insure its proper use.